Review of Vortices in Wildland Fire - Jason M. Forthofer; Scott L. Goodrick (Journal of Combustion)
Vortices are almost always present in the wildland fire environment and can sometimes interact with the fire in unpredictable ways, causing extreme fire behavior and safety concerns. In this paper, the current state of knowledge of the interaction of wildland fire and vortices is examined and reviewed. A basic introduction to vorticity is given, and the two common vortex forms in wildland fire are analyzed: fire whirls and horizontal roll vortices. Attention is given to mechanisms of formation and growth and how this information can be used by firefighters.